(3eLeY GdHMQjf hedJbi GdfgQjfs - (3CMeO Hf Ydj Hf KYdH Hf GdSGYGJj GdHZOGOj , eXaQ GdOjf,J (B694 (3g` s ((3GdeOQSI GdTQYjI GdeSJfUQjI s)
(3ChdgG (B:s
(3GdMeO ddg LGYd GdYdeGA CfLeYkG ddGgJOGA RGgQI hCYdGekG s
(3BNQgG (B:s
(3ceG LYdg ef CfUGQ GdTQY hYdeGFg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B4 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1599s
Keywords: (3Gdabg GdMfajs